Amino acids as modulators of the European seabass, Dicentrarchus labrax, innate immune response: an in vitro approach. Issue 1 (December 2017) - Azeredo, Rita; Serra, Cláudia; Oliva-Teles, Aires; Costas, Benjamín
Abstract Teleost innate immune system is a most developed and powerful system in which fish highly rely throughout their lives. Conditions in aquaculture farms are particularly prone to disease, thus, health and welfare ensuring strategies are an urgent call to which nutrition is gradually becoming a most regarded achievement tool. This study intended to evaluate different amino acids' effect on immune-related mechanisms as well as their potential as enhancers of European seabass, Dicentrarchus labrax, leucocyte functioning. To achieve these goals, primary cultures of head-kidney leucocytes were established and kept in amino acid (glutamine, arginine, tryptophan or methionine) supplemented culture media in two doses. The effects of amino acids treatments were then evaluated after stimulation with eitherVibrio anguillarum orVibrio anguillarum lipopolysaccharides by measuring nitric oxide production, extracellular respiratory burst, ATP and arginase activities, and expression of immune-related genes. Glutamine, arginine and tryptophan showed to be particularly relevant regarding cell energy dynamics; arginine and tryptophan supplementation also resulted in down-regulation of important immune-related genes. Immune responses in cells treated with methionine were generally enhanced but further studies, particularly those of enzymes activity, are essential to complement gene expression results and to better understand this nutrient's immune role in fish.